Potential of forage and grain yield of maize genotypes in the Brazilian semiarid region - Carvalho, Maisa Nascimento [UNESP]; de Oliveira, Tâmara Rebecca Albuquerque; Silveira, Eduarda Santos; de Menezes Santos, Alisson; da Silva, Alex Florentino; de Oliveira, Gustavo Hugo Ferreira (FapUNIFESP (SciELO), 2022)
Maize is importance in the semiarid region due to its forage potential. However, the large number of hybrids on the market hampers the selection of the hybrid by the producer. Given the above, the objective of this paper is to identify genotypes with productive potential for forage and grain production according to the characteristics of the semiarid region of Brazil. Twenty genotypes with different genotypic classes were evaluated in two years (2018 and 2019) in the municipality of Gracho Cardoso, state of Sergipe. The experiments were carried out in a randomized complete block design (RCBD), with two replicates. Genotype characteristics, grain yield, and forage mass were evaluated and the results were estimated using mixed models and GT Biplots. The genotypic classes consisting of topcrosses and intervarietal hybrids showed high average grain yield and the three classes produced equally on average for forage mass. It was observed that the HI, HTC, and V genotypic classes were the most responsive for grain yield, forage mass, and dry matter content, respectively. Therefore, it is concluded that the genetically broad-based hybrids (HTC and HI) were the most promising for the semiarid of region of Sergipe, while interspecific hybrids were the most productive and stable
Keywords: Gt biplot; Hybrids; Multivariate analysis; Zea mays l.